Adiponectin and Leptin Metabolic Biomarkers in Chinese Children and Adolescents - Jie Mi; Mercedes Nancy Munkonda; Ming Li; Mei-Xian Zhang; Xiao-Yuan Zhao; Ponce Cedric Wamba Fouejeu; Katherine Cianflone (Journal of Obesity)
Objective. To evaluate leptin and adiponectin as biomarkers of metabolic syndrome (MS) risk factors even in nonobese children/adolescents. Methods. Serum leptin, adiponectin, leptin:adiponectin ratio, lipids, glucose, and insulin concentrations as well as body size parameters and pubertal development were evaluated in a large population of Chinese children/adolescents (n=3505, 6–18 years, 1722 girls and 1783 boys). Results. Leptin concentration increased while adiponectin decreased with obesity, both were influenced by pubertal development. Central obesity had an additive effect on leptin levels (above obesity alone). Leptin/adiponectin increased 8.4-fold and 3.2-fold in overweight/obesity, and 15.8- and 4.5-fold with obesity plus MS, in early and late puberty, respectively. Even in normal weight children/adolescents, higher leptin and lower adiponectin concentrations associated with increased risk profile. Conversely, overweight/obese with lower leptin or higher adiponectin concentrations had a less compromised metabolic profile. Conclusion. Leptin, adiponectin, and leptin:adiponectin ratio are informative biomarkers for obesity, central obesity, MS, and abnormal metabolic profile even in normal weight children/adolescents.